Changing assessment leading to improving learning using eportefolios - Alfredo Soeiro (2020)
The motivation of this proposal intends to monitor the learning and the skills acquired throughout the attendance of the discipline along the entire semester. This monitoring is based on the preparation by each student of e-portfolios with range of two or three weeks. These e-portfolio documents will be registered in the library of competences acquired with percentage of the respective quantification and with presentation of relevant evidences. The following up of each student route will allow the teacher to personalize the learning needs of each student and to act during the semester along with the course implementation. It is intended to have a closer follow-up of each student studying and especially learning. This close and timely monitoring will allow improvement of teaching, of effective learning and of motivating students through reflection and self-awareness. Evaluating the achievements of this process of pedagogical use of e-portfolios may allow checking the effects, the impact and the success in this pilot attempt. It is intended to collect data about students and teachers ' satisfaction with the approach, consider the impact and effects of the use of this method in the learning achievements of students, realize the lack of acquisition of required skills by employers.